Invasive lobular carcinoma arising in accessory breast tissue - Devine, Catriona; Courtney, Carol-Ann; Deb, Rahul; Agrawal, Amit (BioMed Central, 2013)
Background: Lobular carcinoma in accessory breast tissue is a rare occurrence. We present such a case in a 61-year-old woman.